Pengenalan asam basa melalui praktikum berbasis keterampilan proses sains pada siswa SMP di Kecamatan Herlang - Sumiati Side; Hardin Hardin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Partnership program focused onthe application of practicum based on science process skills forJunior High School or equivalent students. The program aimedto give an overview to the Junior High School or equivalentstudents by doing: 1) efforts to provide mentorship program tothe Junior High School or equivalent students in HerlangDistrict in order to understand process-based skills science, 2)efforts to help the Junior High School or equivalent students inHerlang District to be skilled in practicing practicum based onscience process skills. The targets and outcomes to beachieved in the program were to realize the program on how tomake students capable of practicing based on science processskills and to provide an overview to the teacher in applyingpracticum based on science process skills. Lecture methods,discussion, question and answer, and direct demonstrationswere applied to delivering the training material.